Quantitative T2 and T1ρ mapping are sensitive to ischemic injury to the epiphyseal cartilage in an in vivo piglet model of Legg-Calvé-Perthes disease. Issue 9 (September 2022) - Armstrong, A.R.; Bhave, S.; Buko, E.O.; Chase, K.L.; Tóth, F.; Carlson, C.S.; Ellermann, J.M.; Kim, H.K.W.; Johnson, C.P.
Summary: Objective: To determine if the quantitative MRI techniques T2 and T1ρ mapping are sensitive to ischemic injury to epiphyseal cartilage in vivo in a piglet model of Legg-Calvé-Perthes disease using a clinical 3T MRI scanner. We hypothesized that T2 and T1ρ relaxation times would be increased in the epiphyseal cartilage of operated vs contralateral-control femoral heads 1 week following onset of ischemia. Design: Unilateral femoral head ischemia was surgically induced in eight piglets. Piglets were imaged 1 week post-operatively in vivo at 3T MRI using a magnetization-prepared 3D fast spin echo sequence for T2 and T1ρ mapping and a 3D gradient echo sequence for cartilage segmentation. Ischemia was confirmed in all piglets using gadolinium contrast-enhanced MRI. Median T2 and T1ρ relaxation times were measured in the epiphyseal cartilage of the ischemic and control femoral heads and compared using paired t -tests. Histological assessment was performed on a subset of five piglets. Results: T2 and T1ρ relaxation times were significantly increased in the epiphyseal cartilage of the operated vs control femoral heads (ΔT2 = 11.9 ± 3.7 ms, 95% CI = [8.8, 15.0] ms, P  < 0.0001; ΔT1ρ = 12.8 ± 4.1 ms, 95% CI = [9.4, 16.2] ms, P  < 0.0001). Histological assessment identified chondronecrosis in the hypertrophic and deep proliferative zones within ischemic epiphyseal cartilage. Conclusions: T2 and T1ρ mapping are sensitive to ischemic injury to the epiphyseal cartilage in vivo at clinical 3T MRI. These techniques may be clinically useful to assess injury and repair to the epiphyseal cartilage to better stage the extent of ischemic damage in Legg-Calvé-Perthes disease.